Understanding How Experts Use Bioinformatics Resources - Bartlett, Joan C. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper reports the preliminary findings of a study to understand how experts use bioinformatics resources. These are complex databases of gene or protein sequences, and software tools that manipulate and analyze the data. The experts were seen to follow distinct patterns of resource use, which are quite different from traditional patterns of information-seeking behaviour.